Moderasi Komite Audit Sebagai Peredam Kecurangan Pelaporan Keuangan - Dwianto, Agus; Puspitasari, Diana; Setiawati, Erma (Politeknik Ganesha Medan, 2024)
Financial statement manipulation is a form of fraud that can lead to losses in a company's performance. This study aims to assess the influence of factors in detecting fraudulent corporate financial statements. The research focuses on manufacturing companies listed on the Indonesia Stock Exchange for the period 2017 to 2021. The dependent variable used in this study is fraudulent financial reporting. The independent variables include pressure (comprising financial targets, financial stability, and external pressure), opportunity (comprising ineffective supervision and industry nature), rationalization (comprising auditor turnover and rationalization), competence (measured by director turnover), and arrogance (measured by the frequency of CEO photo appearances). Additionally, the Audit Committee is used as a moderating variable. The test results indicate that financial targets have a significant negative impact on fraudulent financial reporting, while financial stability has a significant positive influence. However, external pressure, ineffective supervision, industry nature, auditor turnover, rationalization, director turnover, and the frequency of CEO photo appearances do not significantly affect fraudulent financial reporting. The implications of this research highlight the importance for companies to carefully monitor and manage their financial targets to avoid fraudulent practices in financial reporting. Furthermore, the role of the Audit Committee in overseeing financial statements needs to be strengthened to mitigate the risk of fraud. The research methodology employed in this study involves panel data regression analysis to examine the influence of the mentioned variables on fraudulent financial reporting.